Be Alert to Diabetes Nephropathy with Cognitive Dysfunction [Letter] - Gan L; Wang C; Liu X (Diabetes, Metabolic Syndrome and Obesity)
Lu Gan, Changde Wang, Xiaoying Liu Neurology Department, Shanghai TCM-Integrated Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 200082, People’s Republic of ChinaCorrespondence: Xiaoying Liu, Email 303425290@qq.com